Extraccion de nitrogeno en seis especies olericolas durante su ciclo de crecimiento - Bugarin Montoya, R.=700 1 Virgen Ponce, M.; Galvis Spinola, A.; Garcia Paredes, D.; Hernandez Mendoza, T.; Bojorquez Serrano, I.; Madueño Molina, A.
(Es, En)
Ilus., 15 ref.
Keywords: HORTALIZAS DE HOJA; LACTUCA SATIVA; LYCOPERSICON ESCULENTUM; PEPINILLO; CAPSICUM ANNUUM; COL; EXTRACCION; NITROGENO; VENEZUELA